Pesantren-Based Madrasah: Curriculum Implementation Model and Integrative Learning - Ihsan, Ihsan (ADDIN, 2019)
This study aims to analyze curriculum implementation design and Islamic Education learning, a variety of curriculum integration and Islamic Education  learning, and pesantren-based madrasah model that is appropriate with National Education Standard and users’ expectations. This research was a qualitative study with a naturalistic paradigm which philosophically referred to phenomenological post-positivism and used social action models. This research was conducted in Kudus Regency with subjects related to institutional reality, curriculum implementation, learning and human resources of Madrasah Aliyah (MA) or Islamic Senior High Schools. The results showed that pesantren or Islamic boarding school is a model of MA management which madrasah and pesantren management are operationally managed in one management system. It means that MA is not only physically located in pesantren, but MA and pesantren are in an integrated organizational and management structure. The purpose of this management system unification is that all educational processes are in a system that allows all teachers and students activities in the same program package. It will ultimately create a holistic education process that produce the quality education output and outcome. Thus, the willingness to make pesantren as an Islamic education curriculum basis is based on the need to maximize the true Islamic education curriculum.